Achievement of low-sensitivity characteristics and robust stability condition for multi-variable systems having an uncertain number of right half plane poles - Yamada, Kou; Hagiwara, Takaaki; Murakami, Iwanori; Yamamoto, Shun; Yamamoto, Hideharu (ECTI Transactions on Electrical Engineering, Electronics, and Communications, 2009)
In the present paper, we consider a design method that provides low-sensitivity control with robust stability for multiple-input/multiple-output continuous time-invariant systems having an uncertain number of right half plane poles. First, the class of uncertainty considered in the present paper is defined and the necessary and sufficient robust stability condition is presented for the system having this class of uncertainty under the assumption that the number of closed right half plane poles of the plant is equal to that of the nominal plant. The relationship between the plant and the nominal plant included in this class of uncertainty is clarified. Using this relationship, we will show the necessary and su±cient robust stability condition for the system having an uncertain number of right half plane poles.